2013
DOI: 10.1093/nar/gkt477
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent cooperative non-specific binding in solid-phase SELEX affinity selection

Abstract: The non-specific binding of undesired ligands to a target is the primary factor limiting the enrichment of tight-binding ligands in affinity selection. Solution-phase non-specific affinity is determined by the free-energy of ligand binding to a single target. However, the solid-phase affinity might be higher if a ligand bound concurrently to multiple adjacent immobilized targets in a cooperative manner. Cooperativity could emerge in this case as a simple consequence of the relationship between the free energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…As the hydrodynamic diameter of a random 80‐mer DNA aptamer is ca . 7.9 nm, this surface density permits aptamer screening anywhere within the theoretically preferred 100:1 to 1000:1 aptamer‐to‐target range, while eliminating the possibility of bridging of aptamers between proximal immobilized targets, an effect that has been shown to confound aptamer selection (Ozer et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…As the hydrodynamic diameter of a random 80‐mer DNA aptamer is ca . 7.9 nm, this surface density permits aptamer screening anywhere within the theoretically preferred 100:1 to 1000:1 aptamer‐to‐target range, while eliminating the possibility of bridging of aptamers between proximal immobilized targets, an effect that has been shown to confound aptamer selection (Ozer et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, many SELEX processes contain steps for target immobilization to solid supports [29]. However, this can introduce nonspecific binding to the aptamer, limiting the enrichment of most specific aptamers during the SELEX process [30]. Many simple isolation methods for bound aptamers in supernatants have been used generally in recent studies [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the molecules cannot always be considered point particles as selections may be affected by molecule size and orientation. 36,37 Although some theoretical work has been done to fill these information gaps, [38][39][40][41][42] most parameters remain experimentally unknown, and researchers have adopted simple intuitive schemes to attempt to create competitiveness and stringency during selections, such as gradually increasing the ratio of library to target molecules (i.e., the fold-excess of library to target) and/or reducing the quantity or concentration of target molecules. These selections are typically performed in one of three ways.…”
Section: -3mentioning
confidence: 99%
“…Recent studies have shown that in certain technologies, many of the core and intuitive assumptions of the SELEX model and basic binding kinetics are not well supported by the binding results. 36,37,[60][61][62]66,67,75 This is likely due to the added complexity of the more sophisticated technologies and immobilization schemes used. Selection techniques are currently evaluated primarily on the number of cycles needed and/or on the binding affinity of the resulting aptamer.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%